E-Commerce Strategic Business Environment Analysis in Indonesia - Aribawa, Dwitya (International Journal of Economics and Financial Issues, 2016)
This research is aim to identified important factors in external business environment that tend to influence company capabilities to achieve objective. It conducts to several E-Commerce in Indonesia. Those companies operate several industries, such as grocery & household retail, fashion retail, electronic & gadget retail and travel agency booking provider. We conduct thematic analysis with quad helix stakeholders approach. It found that the firm faces several external environment factors that affect the business activities. This research concludes that E-Commerce in Indonesia needs to establish strategic action plan to take advantage from opportunities of demographic bonus, arising middle income and broaden the scope of business. To minimizing external limitation, quad helix stakeholders are demanding to covers urgency issues on establishing efficiency in transportation, educating SMEs to engage with e-commerce and demanding of alternatives source of funding. This research recommend that firms in this industry focus on integrating channels of ordering, improving warehousing and delivering process, expanding marketing strategy that focus in knowledge sharing and integrating global supply chain. Keywords: Business Environment; Industry Analysis; E-commerce JEL Classification: F23, M10, M30, F23